BCOR Overexpression in Renal Malignant Solitary Fibrous Tumors: A Close Mimic of Clear Cell Sarcoma of Kidney. (June 2019) - Argani, Pedram; Kao, Yu-Chien; Zhang, Lei; Sung, Yun-Shao; Alaggio, Rita; Swanson, David; Matoso, Andres; Dickson, Brendan C.; Antonescu, Cristina R.
Abstract : BCOR immunoreactivity is a sensitive and highly specific marker for clear cell sarcoma of the kidney (CCSK). However, a subset of adult renal sarcomas which overexpress BCOR are negative for BCOR genetic alterations, including BCOR gene fusions or BCOR -internal tandem duplication, and thus remain unclassified. We report 5 such undifferentiated renal/perirenal sarcomas which raised the differential diagnosis of CCSK due to their morphologic appearance and strong BCOR immunoreactivity, but which on RNA sequencing proved to be malignant solitary fibrous tumors (SFTs). The neoplasms occurred in patients at an age range of 30 to 62 years. Three patients were females and 2 male. Four were primary renal neoplasms while one was perirenal. All 5 neoplasms were cellular, nonpleomorphic, undifferentiated sarcomas with branching capillary vasculature composed of primitive round to ovoid neoplastic cells with scant cytoplasm and nuclei having fine, evenly dispersed chromatin. None of the cases demonstrated the typical hyperchromatic fusiform nuclei, prominent collagen deposition, or hemangiopericytomatous vasculature of SFT. All 5 cases were strongly immunoreactive for BCOR. Three cases were CD34 negative, where the other 2 were only focally CD34 positive. STAT6 was subsequently found to be positive by immunohistochemistry in all 5 cases. In summary, we report a previously unrecognized mimic of CCSK: malignant SFTs with an undifferentiated/small round cell phenotype along with branching capillary vasculature, strong immunoreactivity for BCOR, and minimal or no immunoreactivity for CD34. As CCSK is treated with a specific chemotherapy regimen, this distinction has therapeutic implications. Abstract : Supplemental Digital Content is available in the text.